2007
DOI: 10.1097/scs.0b013e3181534a4d
|View full text |Cite
|
Sign up to set email alerts
|

Topographic and Histologic Characteristics of the Sural Nerve for Use in Nerve Grafting

Abstract: The sural nerve (SN) is a sensory nerve supplying the skin of the lateral and posterior parts of the inferior third of the calf and the lateral side of the foot and is easy to harvest because of its location posterior and superior to the tip of the lateral malleolus. Seventy-one lower limbs from 42 Korean cadavers were dissected to describe the joining type and level of perforated the fascia of the SN. The segments of sural nerve were stained and measured. The communication and joining patterns of the SN forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 16 publications
4
8
0
Order By: Relevance
“…Among previous Korean reports, the frequency of type A observed in our study is similar to that observed by Kim et al (2003), 85.7%, but is somewhat different from those of two other reports, in which the frequencies were 76.9% (Pyun and Kwon, 2008) and 79.1% (Park et al, 2007). However, Pyun and Kwon (2008) described type II in their article as those showing small cross-communications between the MSCN and the peroneal communicating nerve, which we considered to be type A in our study.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Among previous Korean reports, the frequency of type A observed in our study is similar to that observed by Kim et al (2003), 85.7%, but is somewhat different from those of two other reports, in which the frequencies were 76.9% (Pyun and Kwon, 2008) and 79.1% (Park et al, 2007). However, Pyun and Kwon (2008) described type II in their article as those showing small cross-communications between the MSCN and the peroneal communicating nerve, which we considered to be type A in our study.…”
Section: Discussionsupporting
confidence: 51%
“…The various types of sural nerve formation patterns were designated A, B, and C by P'an (1939), although the basic concept had already existed (Kosinski, 1926). This classification has since been used by many investigators, including in recent studies with sporadically suggested subtypes (Park et al, 2007;Ramakrishnan et al, 2015). Based on this classification, type A was the most frequently observed one (86.1%) in this study.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Therefore, we chose the sural nerve as the bridging nerve between the donor and recipient nerves. Considering that the sural nerve graft is superior to some other autologous nerve graft options, it is usually the first choice for nerve reconstruction, especially when repairing longer defects 22–24. Our previous study confirmed the reliability of the sural nerve as a bridging nerve, both in terms of the number of axons and the cross-sectional area 12.…”
Section: Discussionsupporting
confidence: 60%
“…1 The sural nerve is a sensory nerve supplying the skin of the lateral and posterior parts of the foot and is easily harvested due to its location superoposteriorly of the lateral malleolus. 2 A method of harvesting the sural nerve is the "stocking seam" incision, which is made along the course of the nerve. This method leaves an unsightly and, in infants, a wide scar.…”
Section: Introductionmentioning
confidence: 99%